FINDING WAYS OF RECYCLING DUST OF ARC STEEL FURNACES AT THE BELARUSIAN METALLURGIC PLANT. PART 3. EXPERIMENTS ON BRIQUETTING OF DUST OFARC STEEL FURNACES - A. I. Rozhkov; E. V. Ermakova (Литьë и металлургия, 2016)
The article gives an overview of the global experience of recycling dust by briquetting. The advantages and disadvantages of recycling dust with its preliminary briquetting are described. Information about experiments on briquetting of dust generated in different organizations of the Belarusian metallurgy plant with various binders is given. Economic calculations were performed on the basis of technical data obtained during the manufacture of prototypes of briquettes. The results of the calculations showedinexpediency of recycling dust briquetting method because of the low iron content in the dust, high cost of binder and a relatively small rate of ecological tax.